Legal Status of Artificial Intelligence–Based Notarial Deeds: A Juridical Perspective under Indonesian Notarial Law - Richard Adam; Athyana Kamila Syahindra (Greenation Research & Yayasan Global Resarch National, 2026)
This study examines the legal status of artificial intelligence-based notarial deeds in Indonesia and their implications for legal validity. This study aims to analyze the legal status of such deeds and their evidentiary value within the Indonesian notarial legal system. This study uses a normative juridical approach based on statutory and conceptual analysis. The findings indicate that artificial intelligence does not fulfill essential requirements of authenticity, particularly the presence of the parties, the reading of the deed, and its execution before a notary. As a result, such deeds may be classified as private deeds with weaker evidentiary value. The absence of specific regulations creates a legal vacuum, leading to uncertainty. Therefore, adaptive regulatory frameworks are necessary to ensure legal certainty and protection for the parties involved.